Reimagining India : unlocking the potential of Asia's next superpower - Chandler, Clay; Zainulbhai, Adil
"From the world's premier management consultancy McKinsey & Company, a comprehensive collection of essays by the brightest experts on what the new global elite needs to know about modern India"--